The effectiveness of an agile software methodology: empirical evidence on humanistic aspects / Mazni Omar - Omar, Mazni (Institute of Graduate Studies, UiTM, 2012)
Agile methodology emerged in response to the recognition of the importance of humanistic aspects in software engineering (SE). However, there is lack of empirical evidence that supports its effectiveness in SE. The lack of empirical evidence demands more research in this field to generate more empirical data. Therefore, the first aim of this research is to investigate empirically the effect of agile methodology on the members of software development teams. To achieve this goal, a series of longitudinal empirical studies were carried out in both academic and industrial settings. For the academic setting, Universiti Utara Malaysia (UUM) was chosen because participants are representative sample enrolled in a project-based course that requires them to develop an application in a team. Three replicated experiments and two case studies were carried out. To generalize findings, an empirical inquiry in the form of a case study was carried out in a computer centre in Malaysia. The case study focused on four software development teams working on different applications in an organization. Both quantitative and qualitative analyses were used to triangulate and strengthen the empirical results. The humanistic aspect in SE that was addressed was the impact of an agile methodology on work-related wellbeing and positive affectivity of team members.